(In)Satisfação no trabalho de docentes de uma escola estadual: um estudo de caso - Sangoi, Thais Picolin (2015)
This study aimed understands the workers dis(satisfaction) experiences in the education of at-risk children and teenagers. Thus, the specific goals were to know the teachers` dynamic at work; to identify and to describe how the development of work organization occurs in this context; and to identify the factors that interfere on (dis) satisfaction of them. This is a case study with qualitative approach and the scene was a state elementary school located in the center of Rio Grande do Sul. All teachers who work in this scene were asked to participate of the research (n=7). As data collection methods, we used: form of sociodemographic and occupational data; not-participant observation; documental analysis and focus group. The questionnaire of sociodemographic data was assessed through descriptive statistics in order to characterize the participants. For those data obtained from the three sections of focus groups, the content analysis was performed in a seeking for thematic categories development. Observations numbered 25 hours and supported the description of the work dynamic, and the reflection about the object of this investigation together with analysis of documents on school functioning. Data collection was carried out between May and September 2014. Resolution 466/2012 from the Health National Council and Research was followed for researchers and the Ethics Committee approved the project under number 26634714.3.0000.5346. The most of participants were women, aged between 50 and 59 years, with a notable time of work in the teaching and in the institution, with graduate degree completed, with weekly working time at school of 20 hours and with other employment ties. Approximately 95% of participants are little satisfied with the wage received and 95% state that the work conditions impact on their health. Regarding to thematic categories, we found: ―The teachers` dynamic at work‖ and ―The dis(satisfaction) in teacher work‖. The first thematic category approached the occupational dynamic of teachers who work with children and teenagers at social risk, highlighting the conditions that favor its development and the specificities existent in the teachers work routine, as well as the outcomes on these subjects. Satisfaction was associated to the recognizing of the work made, to the feeling of being useful on students` life, and to the pleasure about what they (teachers) do. On other hand, dissatisfaction was linked to the lack of support from government entities, and to the interpersonal relationship with co-workers, an issue that also was a cause of satisfaction at work. In this sense, results and analysis of this study may promote grants for the establishing of interventions in order to prevent potential injuries to these teachers health, to improve the work environment of these professionals, and to promote a better quality of teaching.